Transcriptional repression of E‐cadherin in nickel‐exposed lung epithelial cells mediated by loss of Sp1 binding at the promoter. Issue 1 (2nd November 2021) - Zhang, Xiaoru; Tanwar, Vinay Singh; Jose, Cynthia C; Lee, Hyun‐Wook; Cuddapah, Suresh
Abstract: E‐cadherin plays a central role in the stability of epithelial tissues by facilitating cell‐cell adhesion. Loss of E‐cadherin expression is a hallmark of epithelial‐mesenchymal transition (EMT), a major event in the pathogenesis of several lung diseases. Our earlier studies showed that nickel, a ubiquitous environmental toxicant, induced EMT by persistently downregulating E‐cadherin expression in human lung epithelial cells and that the EMT remained irreversible postexposure. However, the molecular basis of persistent E‐cadherin downregulation by nickel exposure is not understood. Here, our studies show that the binding of transcription factor Sp1 to the promoter of E‐cadherin encoding gene, CDH1, is essential for its expression. Nickel exposure caused a loss of Sp1 binding at the CDH1 promoter, resulting in its downregulation and EMT induction. Loss of Sp1 binding at the CDH1 promoter was associated with an increase in the binding of ZEB1 adjacent to the Sp1 binding site. ZEB1, an EMT master regulator persistently upregulated by nickel exposure, is a negative regulator of CDH1 . CRISPR‐Cas9‐mediated knockout of ZEB1 restored Sp1 binding at the CDH1 promoter. Furthermore, ZEB1 knockout rescued E‐cadherin expression and re‐established the epithelial phenotype. Since EMT is associated with a number of nickel‐exposure‐associated chronic inflammatory lung diseases including asthma, fibrosis and cancer and metastasis, our findings provide new insights into the mechanisms associated with nickel pathogenesis.